A Comparison of Negative Compressibility between 3D Cellular Models Constructed by 2D Hinging Wine‐Rack and Hexagonal Honeycomb Mechanisms. Issue 6 (3rd March 2020) - Ma, Meng; Li, Jinrui; Yang, Lu; Zhou, Xiaoqin
Abstract : Herein, two kinds of 3D hexagonal honeycomb equivalent models are proposed, enlightened by the octahedron model constructed by the wine‐rack mechanism. They differ in their unit‐cell arrangement forms, which are array and homogeneous arrangements, respectively. Referring to the analysis of the octahedron model, the expressions of compressibility properties of the two new models are given and the conditions for obtaining negative compressibility are analyzed. Comparing these two models with the octahedron model, it is found that although the three models are quite different in externality, they have similar mechanical properties (Young's modulus, Poisson's ratio, and compressibility), and all have image symmetry in both horizontal directions. Further analysis shows that these three models are so unified that they can be expressed by a more general model, from which another model with negative compressibility can be deduced. Finally, a new method to improve negative compressibility property is concluded from comparing the three models, that is, increasing the number or length of rods without deformation in vertical direction can effectively improve negative compressibility property in this direction and weaken negative compressibility property in the other two directions. Abstract : Herein, two 3D hexagonal honeycomb equivalent models (columns 3, 4) are proposed, enlightened by the octahedron model (column 1). It is found that the three models can be expressed by a more general model, from which another model (column 2) can be deduced. These models have image symmetry, and all have negative linear compressibility and negative area compressibility.